Evaluation of Communication and Safety Behaviors During Hospital-Wide Code Response Simulation. Issue 1 (February 2022) - Ren, Dennis M.; Abrams, Anna; Banigan, Maureen; Batabyal, Rachael; Chamberlain, James M.; Garrow, Amanda; Izem, Rima; Nicholson, Laura; Ottolini, Mary; Patterson, Mary; Sarnacki, Rachel; Walsh, Heather A.; et al.
Abstract : Introduction: To understand the baseline quality of team communication behaviors at our organization, we implemented institution-wide simulation training and measured the performance of safety behaviors of ad hoc teams in emergent situations. Methods: Clinicians participated in 2 interprofessional video-recorded simulation scenarios, each followed by debriefing. Using a standardized evaluation instrument, 2 reviewers independently evaluated the presence or absence of desired team safety behaviors, including escalating care, sharing a mental model, establishing leadership, thinking out loud, and identifying roles and responsibilities. We also scored the quality of sharing the mental model, closed-loop communication, and overall team performance on a 7-point scale. Discordant reviews were resolved with scoring by an additional reviewer. Results: A total of 1404 clinicians participated in 398 simulation scenarios, resulting in 257 usable videos. Overall, teams exhibited desired behaviors at the following frequencies: escalating care, 85%; sharing mental models, 66%; verbally establishing leadership, 6%; thinking out loud, 87%; and identifying roles and responsibilities, 27%. Across all reviews, the quality of the graded behaviors (of 7 points) was 2.8 for shared mental models, 3.3 for closed-loop communication, and 3.2 for overall team performance. Conclusions: In a simulation setting with ad hoc teams, there was variable performance on completing safety behaviors and only a fair quality of graded communication behaviors. These results establish a baseline assessment of communication and teamwork behaviors and will guide future quality improvement interventions.